Construction of the Au Nanoparticle/Graphene Oxide/Au Nanotube (AuNP/GO/AuNT) Sandwich Membrane for Surface-Enhanced Raman Scattering Sensing - Zhang, Haibao (Langmuir : the ACS journal of surfaces and colloids, 2024)
Au nanotube-based composite membrane served as surface-enhanced Raman scattering (SERS) substrate with an ultralarge aspect ratio possesses an excellent flexibility and widely tunable surface plasmon resonance, and by introducing graphene oxide (GO) as a spacer layer, the SERS enhancement of the composite membrane is obviously better than those from the individual blocks of the Au nanotubes (AuNTS) membrane and the Au nanoparticle/graphene oxide (AuNP/GO) membrane. Such a "sandwich" (AuNP/GO/AuNT) structured membrane has a high SERS sensitivity and a wide tunability by controlling the size of Au nanoparticles and the thickness of graphene oxide, and the detection limits of the AuNP/GO/AuNT substrate for R6G and NBA are as low as 10-12 and 10-7 M, respectively; the large enhancement is attributed to the adsorption and chemical mechanism of graphene oxide and the physical mechanism of the Au nanoparticles and nanotubes (the electromagnetic field coupling between them)